Prospecção tecnológica na cadeia produtiva do cumaru (Dipteryx Odorata) - Barbosa, Amanda Guedes (Brasil, 2024)
This study focuses on the Amazonian biodiversity and the technological development potential related to cumaru (Dipteryx odorata), a legume rich in coumarin with applications in the perfume, cosmetics, phytotherapy, and food industries, in addition to its valuable timber. The study aimed to conduct a comprehensive scientific and technological prospecting, mapping patents and reviewing the literature related to cumaru to identify developed technologies, depositors, and countries of patent protection. The adopted method included the analysis of patent documents and a systematic review of terms related to cumaru, using Questel Orbit Intelligence and the Portal de Periódicos Capes as databases. Technological prospecting is a valuable tool to guide innovation and support decision-making, allowing the visualization of global technological guidelines and contributing to sustainable development. The analysis of cumaru-related patents revealed an active field of intellectual property. The interest in cumaru-related patents grew significantly after the 2000s, reflecting an increase in research and innovation. Several entities from different sectors are involved in patent protection, evidencing the versatility of cumaru. The main technological domains include Fine Organic Chemistry, Pharmaceuticals, Basic Materials Chemistry, Food Chemistry, and Chemical Engineering. The main countries protecting cumaru-related patents are the United States, European countries, Asia, and Brazil. These conclusions highlight the global and diversified interest in cumaru, across various industries. The study emphasizes the importance of exploring cumaru in a sustainable and technologically advanced way, promoting investments in the primary sector in the Amazon region and contributing to the region's economic and social development.